The Family Socio-economic Life by Female Workers in Langgudu Sub-District, Bima Regency - Faidin, Nahrul; Suyahmo, Suyahmo; Atmaja, Hamdan Tri (Universitas Negeri Semarang, 2020)
The low economy is the reason for mothers to work abroad, which reduces the quality of parenting in the family. The research objective was to determine social life, economic life and parenting styles. This research uses qualitative methods with descriptive analysis. Data collection techniques are interviews, observation and documentation. The informants in this study are; upper class families, 2) Middle class families, 2) and Lower class families, 2). The result is, (1) Social life from the aspects of education, lifestyle and moral behavior runs well, while lower class families are not taught morally, (2) Economic life includes income from trade and labor and is used for consumption needs and children's schooling. needs, (3) Parenting is done by showing positive behavior, organizing activities and advising children. Meanwhile, lower class family care is not carried out. Family social life is based on the economic abilities and knowledge of parents. Economic life is a source of income from various assets and professions and income is used for secondary and primary needs. Parenting is correct, but the care scheme for lower-class families is hampered because parents earn a living outside the home.